Penggunaan Aplikasi Google Maps Sebagai Media Promosi UMKM di Nagari Batang Arah Tapan - Rindiyani; Nuzuli, Ahmad Khairul; Oktaviana, Winda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
Nagari Batang Arah Tapan, which is in the Basa Ampek Balai Tapan sub-district, where the majority of the population owns UMKM businesses but has limited knowledge in marketing and promotion. Of the many UMKM in Nagari Batang Arah Tapan, there are obstacles that are often experienced, namely media promotion facilities for the location and product information produced, in this case a google maps UMKM mapping application is needed in Nagari Batang Arah Tapan as a means of finding UMKM locations. The purpose of the service is to socialize the use of Google Maps to the people in Nagari Batang Arah Tapan who have businesses. The results of the dedication carried out were an increase in ability to carry out promotions and marketing, especially the use of Google Maps as a means of promotional media. The impact after the implementation of the UMKM Socialization experienced an increase in knowledge of using the Google Maps application by 45% compared to the pretest score